Development and application of a lightweight educational technology on the national childhood immunization calendar in Brazil (Research, Society and Development, 2021)
The National Immunization Program was created with the aim of promoting population health. With regard to children, whose immunization represents an inviolable right, it is essential to constantly sensitize those responsible about the issue, mitigating the possibility of the return of eradicated diseases. Thus, this article aimed to describe an academic experience that took place during a health education action, through the creation and application of a light technology aimed at parents/guardians regarding the importance of vaccination of children. It was noticed in the participants' feedback that the activity was essential for obtaining and consolidating knowledge about the topic addressed. This study enabled the understanding of aspects related to vaccine refusal in Brazil, having great significance for academics, since they were able to act directly in this reality.